2016
DOI: 10.1007/s11069-016-2725-y
|View full text |Cite
|
Sign up to set email alerts
|

Impact of DEM-derived factors and analytical hierarchy process on landslide susceptibility mapping in the region of Rożnów Lake, Poland

Abstract: Choosing appropriate landslide-controlling factors (LCFs) in landslide susceptibility mapping (LSM) is a challenging task and depends on the nature of terrain and expert knowledge and experience. Nowadays, it is very common to use digital elevation model (DEM) and DEM-derivatives, as a representation of the topographic conditions. The objective of this study is to explore topography in depth and simultaneously reduce redundant information within DEM-derivatives using principal component analysis. Moreover, thi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
57
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 90 publications
(65 citation statements)
references
References 61 publications
(148 reference statements)
0
57
1
Order By: Relevance
“…Aleotti and Chowdhury, 1999;Guzzetti et al, 1999;Wang et al, 2005). The present study uses fuzzy logic as the method is computationally simple, can consider highly uncertain data inputs, has been shown to match or outperform other approaches (Pradhan, 2011;Bui et al, 2012;Pourghasemi et al, 2012), and, importantly for this study, is fast to apply. While other approaches, such as multivariate statistical analysis, may provide more accurate landslide forecasts, we argue that the marginal gain in forecast accuracy for such approaches is outweighed by the time required to undertake them.…”
Section: Methods and Data Analysismentioning
confidence: 77%
See 1 more Smart Citation
“…Aleotti and Chowdhury, 1999;Guzzetti et al, 1999;Wang et al, 2005). The present study uses fuzzy logic as the method is computationally simple, can consider highly uncertain data inputs, has been shown to match or outperform other approaches (Pradhan, 2011;Bui et al, 2012;Pourghasemi et al, 2012), and, importantly for this study, is fast to apply. While other approaches, such as multivariate statistical analysis, may provide more accurate landslide forecasts, we argue that the marginal gain in forecast accuracy for such approaches is outweighed by the time required to undertake them.…”
Section: Methods and Data Analysismentioning
confidence: 77%
“…This is especially true for lower income countries such as Nepal, where the necessary data either may not exist or may not be readily accessible. Further, we have shown that accurate landslide models can be created without the need for these factors, so long as other important factors, in particular slope angle, are considered (also see Pawluszek and Borkowski, 2017, for a comparison of the role of topographic factors and non-topographic factors). Of course, if these datasets do exist, then they can easily be incorporated into the factor analysis.…”
Section: Other Predisposing Factorsmentioning
confidence: 99%
“…Aleotti and Chowdhury, 1999;Guzzetti et al, 1999;Wang et al, 2005). The present study uses fuzzy logic as the method is computationally simple, can consider highly uncertain data inputs, has been shown to match or outperform other approaches (Pradhan, 2011;Bui et al, 2012;Pourghasemi et al, 2012), and, importantly for this study, is fast to apply. While other approaches, such as multivariate statistical analysis, may provide more accurate landslide forecasts, we argue that the marginal gain in forecast accu-racy for such approaches is outweighed by the time required to undertake them.…”
Section: Methods and Data Analysismentioning
confidence: 77%
“…Qualitative models are mostly based on expert opinion, whereas quantitative models are data-driven, which makes them more reliable. The quantitative approaches include several kinds of techniques such, including statistical, deterministic, and other approaches [51][52][53]. In the case of statistical approaches, it is assumed that the parameters affecting landslide events in the past will be the same in future [54], and these analyses can be categorized into bivariate and multivariate [49].…”
Section: Landslide Susceptibility Mappingmentioning
confidence: 99%
“…In bivariate analysis, the factors affecting landslides are compared with landslide inventory data by providing weights based on landslide causative factors. The most frequently used methods in bivariate models are overlay, index-based, and weight-of-evidence analyses [8,51,55]. Bui et al [6] performed a comparison between a bivariate approach (statistical index) and a multivariate approach (logistic regression) for Vietnam, and found equal forecasting capability.…”
Section: Landslide Susceptibility Mappingmentioning
confidence: 99%